EVALUATION OF PLANNING AND DESIGN OF BOGORCIAWI- SUKABUMI TOLL ROAD SECTION 2 - Naduma, Kesia
Bogor-Ciawi-Sukabumi Toll Road which passes through Bogor City, Bogor Regency, Sukabumi Regency, and Sukabumi City is a continuation of the Jagorawi Toll Road that has been operating. Evaluation of the design was by comparing the results that have been carried out previously in the needs to anticipate changes with traffic demand. Moreover, implemented with technical design and cost estimates on Bogor-Ciawi-Sukabumi toll road Section 2. Traffic modeling is carried out with 4-stage modeling, start with demand forecasting, O-D matrix, mode choice, and assessment to the network. The assesment to the network system is carried out using EMME 4 with a results of traffic performance in the form of flow, free flow speed, and degree of saturation on toll roads. The traffic flow then becomes the basis for geometric design of roads, pavements, and estimating costs. The results are geometric design with a configuration of 4/2 D until 2050 and it needs a widening to 6/2 D until 2060. For pavement design, rigid pavement will be used with K-350 concrete slabs and a thickness of 30 cm. The estimated cost of the construction was Rp1,331,093,615,278.